Reframing Classical Mechanics: An AKSZ Sigma Model Perspective - Thomas Basile; Nicolas Boulanger; Arghya Chattopadhyay (Universe, 2025)
The path-integral re-formulation due to E. Gozzi, M. Regini, M. Reuter, and W. D. Thacker of Koopman and von Neumann’s original operator formulation of a classical Hamiltonian system on a symplectic manifold M is identified as a gauge slice of a one-dimensional Alexandrov–Kontsevich–Schwarz–Zaboronsky sigma model with target <semantics>T*(T[1]M×R[1])</semantics>.